The role of polypropylene matrix in cyclic bending coupled thermal effects. Issue 7 (7th April 2017) - Boccardi, Simone; Carlomagno, Giovanni Maria; Simeoli, Giorgio; Russo, Pietro; Meola, Carosena
Abstract : Infrared thermography is used to visualize temperature variations which are linked to thermoelastic effects developing over the surface of a cantilever beam undergoing deflection under cyclic bending tests. Several specimens are fabricated of thermoplastic composite materials, which involve change of matrix and/or reinforcement. More specifically, the matrix is either a pure polypropylene, or a polypropylene modified with the addition of a certain percentage of compatibilizing agent (grafted); the reinforcement being made of woven glass, or jute, fibers. Cyclic bending tests are carried out with the aid of an electromechanical actuator. One surface of the specimen is continuously viewed by an infrared imaging device during deflection. The suitability of infrared thermography to distinguish the small surface temperature variations, depending on both matrix and reinforcement type, has been previously demonstrated. In this work, the matrix is separately analyzed to add information about its role when coupled with either glass, or jute, and in the presence of a certain percentage of a grafting agent. POLYM. ENG. SCI., 57:680–684, 2017. © 2017 Society of Plastics Engineers